Kingdom of Swaziland : Staff Monitored Program-Staff Report; Staff Supplement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The Swaziland economy continues to suffer from the global economic crisis and an overvalued real exchange rate. The fiscal crisis is starting to affect external stability. Notwithstanding the fiscal crisis, banks continue to remain well capitalized and profitable. The 2011-12 budget promises to make significant progress in fiscal adjustment while safeguarding priority expenditures. The government is taking ambitious measures to cut the wage bill in FY2011-12. Improvements in revenue administration by the Swaziland Revenue Authority (SRA) will strengthen revenue collections.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Eswatini, Kingdom of